Paradoxe d'évaporation dans la vallée du fleuve Sénégal - Papa Malick Ndiaye; Ansoumana Bodian; Serigne Bassirou Diop (Physio-Géo)
The increase in temperatures in a context of climate change should be accompanied by an increase in evaporation or evapotranspiration (ET0). However, studies have shown a decrease in evaporation (or evapotranspiration) in certain regions of the world. This contrast between the decrease in evaporation and the increase in temperature, which varies according to the climatic zones, is known as the "evaporation paradox". The objective of this work is to examine the causes in the climatic context of the Senegal River Valley. The climatic data (evaporation, rain, temperature, relative humidity, insolation) observed at the stations of Bakel, Podor, Matam and Saint-Louis were used over the period 1981-2015. The methodology includes: 1/ the detection of ruptures by the PETTITT test, 2/ the analysis of the relationship between evaporation / evapotranspiration and climatic variables by the PEARSON correlation test, 3/ the detection of trends in Evaporation / ET0 and climate variables by the MANN-KENDALL test and SEN’s slope. The breaks in evaporation and evapotranspiration are respectively identified in the 1990s and 2000s. The PEARSON correlation shows that evaporation and ET0 have their strongest relationship with the relative humidity. MANN-KENDALL's test reveals a significant decrease (p-value ˂ 0.001) in evaporation and a mixed trend (decrease and increase) in reference evapotranspiration. This decrease in evaporation, combined with a significant increase in temperature, highlights the existence of an evaporation paradox in the Senegal river valley. This evaporation paradox is explained here by the significant increase in relative humidity and rainfall, but also by the significant decrease in sunshine hours.